EP 56. Cerebellar learning and its modifiability by alcohol in myoclonus-dystonia. Issue 9 (September 2016) - Werner, E.; Weißbach, A.; Timmann, D.; Brüggemann, N.; Tadic, V.; Klein, C.; Münchau, A.; Bäumer, T.
Abstract : Objectives: To investigate cerebellar learning and its modifiability by alcohol in SGCE mutation-positive myoclonus-dystonia and healthy controls using eyeblink conditioning. Background: Myoclonus-dystonia is an inherited neurological movement disorder characterized predominantly by generalized myoclonic jerks and focal or segmental dystonia with a remarkable decrease of symptoms due to alcohol. This effect has raised the question whether the cerebellum could play an important role in the generation of motor symptoms. Methods: Delay eyeblink conditioning was assessed in 12 SGCE mutation-positive myoclonus-dystonia patients and 16 control subjects on day 1 before (OFF_C2 state) and on day 2 after a single oral ethanol dose (ON_C2 state), calculated according to the Widmark formula to reach a breath alcohol content of 0.8 ‰ (±0.1 ‰ ). For the conditioning paradigm, an air puff applied to the outer canthus of the eye was preceded by a 540 ms tone, the conditioned stimulus, in 10 learning blocks each including 10 paired stimuli (LT1-LT10). The learning paradigm was followed by three extinction blocks (10 stimuli each), in which the single tone was given only (ET1-ET3). To test for differential effects, a multifactorial repeated measures ANOVA was used with the factors STATE (OFF_C2 and ON_C2), BLOCK (LT1-10 and ET1-3) and the in-between subject factor GROUP (patient and controls). Results: The ANOVA showed a significant main effect of the factor GROUP (F1;26) = 7.162, p = 0.013) and BLOCK (F12;312) = 20.181, p < 0.001) and an interaction of the factors STATE x GROUP (F1;26) = 7.793, p = 0.01) (Fig. 1 ) indicating that ethanol has a differential effect in myoclonus dystonia compared to controls. Without the influence of alcohol, compared to healthy controls, myoclonus-dystonia patients revealed a significantly lower learning effect (GROUP (F1;26) = 13.255, p = 0.001) and BLOCK (F9;234) = 12.23, p < 0.001) and an interaction of the factors BLOCK and GROUP (F9;234) = 2.935, p = 0.013) (Fig. 1 A LT1-10) and an altered extinction rate (LT 10 to ET 1, patients 41%–22% and controls 79%–32%). Although conditioning rates under the influence of alcohol did not significantly differ when comparing patients and control subjects, both groups showed a reverse effect comparing the learning effect before and after alcohol administration. While the control group had lower conditioning rates under alcohol, myoclonus-dystonia patients showed an increased eye blink conditioning rate under alcohol influence with a main effect of the factor STATE when assessing cerebellar learning before and after alcohol consumption (F1;11) = 7.921, p = 0.017). Conclusion: Cerebellar learning is impaired in patients with SGCE mutation-positive myoclonus-dystonia and alcohol administration is able to this improves learning effects. This goes along with the clinically evident improvement of motors symptoms after alcohol intake. This study supports the idea of a crucial role of the cerebellum in generating motor symptoms in myoclonus dystonia.